2016
DOI: 10.1016/j.ypmed.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Places where children are active: A longitudinal examination of children's physical activity

Abstract: Using two-year longitudinal data, we examined locations where children spent time and were active, whether location patterns were stable, and relationships between spending time in their home neighborhood and moderate to vigorous physical activity (MVPA). At two time points (2007–2009 and 2009–2011), children living in the metropolitans areas of either San Diego, CA or Seattle, WA wore an accelerometer, and parents recorded their child’s locations for seven days. Across two years, global average proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
2
7
0
1
Order By: Relevance
“…Away from home children were most likely to play at the park or in green spaces. These results align with research using accelerometers and place-logs, which showed that children spent almost 50% of their time at home (24). Other than at home or school, Perry and colleagues found that children primarily spent time at other people's homes or in parks, which also aligns with our ndings.…”
Section: Discussionsupporting
confidence: 90%
“…Away from home children were most likely to play at the park or in green spaces. These results align with research using accelerometers and place-logs, which showed that children spent almost 50% of their time at home (24). Other than at home or school, Perry and colleagues found that children primarily spent time at other people's homes or in parks, which also aligns with our ndings.…”
Section: Discussionsupporting
confidence: 90%
“…22 Our results are partially consistent with those of a longitudinal study conducted in a different region of the United States in which parent-reported home, school, and neighborhood were common physical activity locations; however, unlike the present study, children also commonly engaged in physical activity in indoor and outdoor recreational facilities and parks. 23 These differences could be due in part to differences in study methodology and perhaps regional differences in preferences or availability of/access to facilities.…”
Section: Physical Contexts Of Physical Activitiesmentioning
confidence: 99%
“…For example, one research team reported that one children are physically active primarily outdoors away from home, followed by indoors at home, with other locations such as a gym or recreation facility being less common . Another found that home/neighborhood and school were the most common locations, whereas a third study found that indoor and outdoor community facilities and parks were the most common locations for physical activity …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As áreas próximas à residência das crianças revelam-se como potenciais ambientes promotores da sua AF (MITCHELL et al, 2016;PERRY et al, 2016). A percepção parental sobre os arredores da residência da criança pode ser um facilitador da AF moderada-vigorosa (KURKA et al, 2015) e da mobilidade independente das crianças (SANTOS et al, 2013).…”
Section: Introductionunclassified